Research secondment at Széchenyi István University of Győr, as part of the Erasmus project titled "overcoming the digital divide in Europe and Southeast Asia” - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
Dr. Azlina Hanif, a senior lecturer in Economics at Arshad Ayub Graduate Business School underwenta research secondment at Széchenyi István University of Gyór, Hungary, as part of the ERASMUS project titled 'Overcoming the Digital Divide in Europe and Southeast Asia." Over the course of one month, she contributed to the project's Work Package 3, focusing ona quantitative analysis of the role of institutions and market structure in shaping the growth impact of digital goods (ICT). Collaborating with the project research team at Széchenyi István University, Dr. Azlina's work aimed to provide valuable insights into how digital goods can drive growth across different regions, particularly through the lens of institutional frameworks and market dynamics.